Associations between quantitative sleep EEG and subsequent cognitive decline in older women. (5th March 2018) - Djonlagic, Ina; Aeschbach, Daniel; Harrison, Stephanie Litwack; Dean, Dennis; Yaffe, Kristine; Ancoli‐Israel, Sonia; Stone, Katie; Redline, Susan
Summary: The pathophysiological processes of Alzheimer's dementia predate its clinical manifestation. Sleep disturbances can accelerate the aging process and are common features of dementia. This study examined whether quantitative sleep electroencephalogram changes predate the clinical development of mild cognitive impairment and/or incident dementia. We collected data from a nested case‐control sample of women (mean age 83 years) from the Sleep and Cognition Study, an ancillary study to the longitudinal Study of Osteoporotic Fractures, who were characterized as cognitively normal at the time of a baseline polysomnography study (Study of Osteoporotic Fractures visit 8) based on a Mini‐Mental Status Exam (MMSE) score >24. Cases ( n = 85) were women who developed new mild cognitive impairment or dementia by objective cognitive testing 5 years after polysomnography. Controls were women with no mild cognitive impairment/dementia ( n = 85) at baseline or at follow‐up. Differences in electroencephalogram absolute and relative power density were observed between the two groups. Specifically, higher electroencephalogram power values were found in the dementia/mild cognitive impairment group, for the alpha ( p = .01) and theta bands ( p = .04) in non‐rapid eye movement sleep, as well as alpha ( p = .04) and sigma ( p = .04) bands in rapid eye movement sleep. In contrast, there were no group differences in traditional polysomnography measures of sleep architecture and sleep stage distribution, as well as sleep apnea and periodic limb movement indices. Our results provide evidence for quantitative electroencephalogram changes, which precede the clinical onset of cognitive decline and the diagnosis of dementia in elderly women, and support the application of quantitative sleep electroencephalogram analysis as a promising biomarker for imminent cognitive decline.